The Effectiveness of Using Instructional Videos on Learning Outcomes in Creative Evening Hairstyling Practice Among Grade XI Beauty Cosmetology Students at SMK Negeri 3 Tangerang - Salsabila Ramadhanti; Aniesa Puspa Arum; Neneng Siti Silfi (Vifada Journal of Education, 2026)
This study aims to examine the effectiveness of instructional video usage on learning outcomes in creative evening-style bun hairstyling practice among Grade XI Beauty Cosmetology students at SMK Negeri 3 Tangerang. Instructional videos are implemented as a learning medium to support students’ understanding of procedural steps in practical competencies that require high psychomotor skills. The research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 29 valid students selected through purposive sampling from a population of 31 students. Data were collected using cognitive tests (pretest and posttest) and psychomotor performance assessments based on structured rubrics covering preparation, technique, cleanliness, time accuracy, and final result. The cognitive data were analyzed using descriptive statistics, normality tests, and Wilcoxon Signed-Rank Test, followed by effect size analysis. The results showed that there was no statistically significant difference between pretest and posttest scores (p = 0.315), with a small effect size (r = 0.186), indicating that the video functioned mainly as a reinforcing medium for theoretical understanding. However, psychomotor assessment results demonstrated a high level of student achievement, with a mean score of 89.14 and 100% of students achieving competency above the minimum mastery criteria (KKM ≥ 80). The findings indicate that instructional video usage is highly effective in improving students’ practical skills in hairstyling practice, although its impact on cognitive improvement is limited due to already high baseline knowledge levels. This study highlights the importance of integrating video-based learning to enhance vocational skill mastery in Beauty Cosmetology education.